2017
DOI: 10.1177/0194599817742579
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Findings on FDG PET/CT in Head and Neck Cancer

Abstract: Objective 18F-fluoro-deoxy-glucose positron emission tomography/computed tomography (FDG PET/CT) imaging is common in head and neck cancer and often identifies incidental findings that necessitate additional patient evaluations. Our goal was to assess the frequency and nature of these incidental imaging findings on FDG-PET/CT. Study Design Retrospective cohort study. Setting Tertiary medical center. Subjects and Methods All patients with head and neck cancer who had undergone FDG-PET/CT imaging between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
6
20
1
Order By: Relevance
“…The authors were able to find one other study investigating the same topic specifically in head and neck cancers. This was undertaken in the USA, where Britt et al report rates of 14.6% suspected malignancy, with 4.1% (12/293) confirmed new unrelated malignancy (5 were thyroid cancer; 2, lung cancer; 2, gastrointestinal; and 1 each of HNC, lymphoma, and genitourinary cancer) [ 7 ], a rate which is similar to our UK cohort.…”
Section: Discussionsupporting
confidence: 83%
“…The authors were able to find one other study investigating the same topic specifically in head and neck cancers. This was undertaken in the USA, where Britt et al report rates of 14.6% suspected malignancy, with 4.1% (12/293) confirmed new unrelated malignancy (5 were thyroid cancer; 2, lung cancer; 2, gastrointestinal; and 1 each of HNC, lymphoma, and genitourinary cancer) [ 7 ], a rate which is similar to our UK cohort.…”
Section: Discussionsupporting
confidence: 83%
“…This number corresponds well with the 3.88% of incidental ndings in a population of high-risk primary breast cancer in the same institution and time [10]. Other studies on different cancers have also found between 1-8% of additional malignancies at [ 18 F]FDG-PET/CT [9,[15][16][17][18].…”
Section: Accuracysupporting
confidence: 77%
“…Additionally, MRI is substantially hampered by dental artifacts, which is quite relevant for the visualization of the oral cavity and some oropharyngeal tumors. Moreover, according to our experience, dedicated highresolution PET/CT of the head and neck region appears at least noninferior or even superior to MRI and CT for the detection of pathologically involved lymph nodes and distant metastases and helps to detect second primary malignancies [9,10,19,[11][12][13][14][15][16][17][18]. On the other hand, the anatomical resolution, tissue contrast and availability of different functional imaging sequences make MRI the superior modality for the identification and demarcation of primary tumors [20].…”
Section: Discussionmentioning
confidence: 99%